If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3r + -1(1 + -1) = r + 8 Combine like terms: 1 + -1 = 0 3r + -1(0) = r + 8 Multiply -1 * 0 3r + 0 = r + 8 Anything times zero is zero. 3r + 0 = r + 8 Reorder the terms: 0 + 3r = r + 8 Remove the zero: 3r = r + 8 Reorder the terms: 3r = 8 + r Solving 3r = 8 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 3r + -1r = 8 + r + -1r Combine like terms: 3r + -1r = 2r 2r = 8 + r + -1r Combine like terms: r + -1r = 0 2r = 8 + 0 2r = 8 Divide each side by '2'. r = 4 Simplifying r = 4
| 5x-(x+3)=33 | | -48=(-9)-13n | | -(3x+3)+4x=12 | | -g=2/3x-17 | | -2x+34=2 | | 4X+35+X+20=180 | | -423=8(3+7p)+1 | | 9/10-4/5p=5/6 | | 6x-30-40=20 | | 3(w-2)=-8 | | 3*r-(1-1)=r+(24/3) | | -2(-1+n)=18 | | ((27p^6)^5/3) | | 15.8x+.5x-130.4=16.3 | | (2x+5)+(x+10)=0 | | 1/9g=-15 | | 3/2x+x/5=17 | | 4.1/5=3p | | 9x+3x=70 | | 225*67/75*1/9 | | (27p^6)^5/3 | | 2079=2x+2(2x-5)+5x+10 | | 3(1-a)=-a+5 | | -98=-28x+2x^2 | | 5(7+n)=37+7n | | 27t+1t=-8t | | 7z-4=13+z | | (a+2)(a-4)+10=(-a-2)(6-a) | | -9-x=-4 | | -5/20c=20 | | 5/5-5/11 | | w/w-3-2w/2w-3=w-5/2w^2-9w+9 |